ANTIDEPRESSANT-LIKE ACTIVITY OF FLOWERS OF TECOMELLA UNDULATA IN MICE SUBJECTED TO CHRONIC UNPREDICTABLE MILD STRESS - Dhingra, Dinesh; Deepak, Deepak (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Flowers of Tecomella undulata have been reported to be a rich source of flavonoids such as rutin and quercetin. The present study was designed to evaluate the effect of ethanol extract of flowers of T. undulata on chronic unpredictable mild stress (CUMS)-induced depression in Swiss young male albino mice. Methods: The mice were subjected to CUMS for 21 successive days. Ethanol extract of the flowers (50, 100, and 200 mg/kg, p.o.) and fluoxetine (20 mg/kg, p.o.) per se was administered for 21 successive days to separate groups of unstressed and stressed mice. Tail suspension test (TST) and sucrose preference test were used to evaluate the effect of the extract on depression-like behavior in mice. Results: Extract of flowers of T. undulata (100 and 200 mg/kg) significantly decreased immobility period of stressed mice in TST, indicating significant antidepressant-like activity of the extract. Stress-induced reduced sucrose preference was significantly restored by the extract. There was no significant effect on locomotor activity of mice by the extract and fluoxetine. The extract significantly reversed stress-induced increase in brain malondialdehyde levels; plasma nitrite and corticosterone levels; and also significantly reversed the stress-induced decrease in reduced glutathione and catalase levels. There was no significant effect of the extract on brain MAO-A activity in both unstressed and stressed mice. Conclusion: These results indicated that ethanol extract of flowers of T. undulata showed significant antidepressant-like activity in mice subjected to CUMS, probably through alleviation of oxidative stress and decrease in plasma corticosterone levels.